SISTEM INFORMASI PENJUALAN DAN TABUNGAN HEWAN QURBAN (Studi Kasus : DKM Masjid Baitirrahman) - Yus Jayusman; Abdurrahman Abdurrahman; Rahmat Jaenal (LPPM STMIK BANDUNG, 2022)
The information system for selling and saving qurban animals is a website-based application designed to make it easier for people to save qurban animals so they don't have to bother having to go to the caretaker but now it is easy to do it anywhere and anytime, this information system provides a forum for qurban animal sellers so that traders do not again selling sacrificial animals to the market but it can be done online by using this information system. It is hoped that the DKM management can provide a detailed report and do not need to wait 1 to 3 for the presentation. Therefore, the purpose of this information system on selling and saving sacrificial animals is to make it easier for all elements of society who want to save and sell their animal savings. Keywords: Sales, Qurban Savings, information system